Response of Cretaceous Palynological Records to Regional Tectonic Events and Global Climate Change in Liupanshan Basin, Northwest China - Bohua Liu; Fang Wu; Lijie Wei; Zhenhong Li; Xiaopeng Dong (Applied Sciences)
The transition of the East Asian tectonic system during the Jurassic-Cretaceous period has had a profound influence on the paleoclimatic evolution in Northwest China. However, there are few studies on the climatic response to the tectonic events of this period. This study is based on the palynological analysis of the Lower Cretaceous Madongshan Formation in the southern Liupanshan Basin, Northwest China, and the summary of published data. It establishes a stratigraphic framework for the Early Cretaceous of the Liupanshan Basin and adjacent areas. It integrates the global Lower Cretaceous paleoclimatic background with the Middle Jurassic-late Lower Cretaceous sedimentary facies and the paleogeographic pattern of the Liupanshan Basin and the adjacent Ordos Basin. This integration aims to explore the climatic background differences between the Liupanshan and the Ordos Basin and to deduce the paleoclimatic response to tectonism and global paleoclimatic events. We determine an Aptian-Albian age for the Madongshan Formation in the Liupanshan Basin. This formation can be divided into three palynological assemblage zones from bottom to top (Zones I–III). In general, the climate changed from dry to wet, and the climate in Zone I was arid. In contrast, the adjacent Ordos Basin remained in a cool and humid environment during the sedimentation corresponding to Zone I. This points to a significant influence of the Jurassic-Cretaceous tectonic uplift on the regional climate evolution. Furthermore, the climate of Zone III became relatively humid in response to a global climatic cooling event at the Aptian-Albian transition. The study showed that the global climate change and regional tectonic events jointly influenced the regional climate evolution. Moreover, global climate change affected the paleoclimatic evolution of Northwest China later than the regional tectonic activities.